GAMBARAN SELF-ESTEEM PADA PASANGAN SUAMI-ISTRI YANG MENGALAMI INFERTILITAS - Elvina Elvina; Venie Viktoria Rondang Maulin (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2013)
The presence of children in the marriage is considered by society as ordinary and desired in marriage. Gender stereotypes, the nature of women, as well as the view of the prevailing patriarchal culture in Indonesia strengthens the desire and need for the couple to have children in a marriage. But some couples experience infertility. Infertility refers to the failure of a couple to have a child after 24 months or so on for having a child with sexual intercourse without using contraception. The experience of infertility can be viewed differently by individuals who experience it. Self-esteem in this study extend from the relation between the dimensions of competence and worthiness that refers to the theory of self-esteem by Mruk and Branden. Data collection was conducted with an unstructured interview. Characteristics of participants in this study are couples that have been trying to have a child with sexual intercourse without using contraception for 2 years or more, but not getting the first child. The number of participants who contributed to this study are two couples were interviewed separately, both among husband and wife and between couples. The results of this study ilustrates that self-esteem, a husband and wife who experience infertility depends on how important the presence of children for each individual. Self worth and social factors that are owned by each individual has an important role in the self-esteem of both husband and wife to experience infertility. In addition, spousal support also plays a role in the self-esteem of each individual.